Optimizing Survival and the Changing Landscape of Targeted Therapy for Intermediate and Advanced Hepatocellular Carcinoma: A Systematic Review. (8th September 2020) - Lim, Howard; Ramjeesingh, Ravi; Liu, Dave; Tam, Vincent C; Knox, Jennifer J; Card, Paul B; Meyers, Brandon M
Abstract: Background: Systemic therapy for hepatocellular carcinoma (HCC) consisting of the tyrosine kinase inhibitor sorafenib has remained unchanged for over a decade, although results from phase III targeted therapy trials have recently emerged. This review considers available phase III evidence on the use and sequencing of targeted therapy for intermediate and advanced non-locoregional therapy (LRT) eligible HCC and discusses implications for clinical practice. Methods: Published and presented literature on phase III data reporting on targeted therapy for advanced HCC that was not eligible for loco-regional therapies was identified using the key search terms "hepatocellular cancer" AND "advanced" AND "targeted therapy" AND "phase III" OR respective aliases (PRISMA). Results: Ten phase III trials assessed targeted therapy first-line and eight following sorafenib. In the first-line, atezolizumab plus bevacizumab statistically significantly improved overall survival (OS) and patient-reported outcomes (PROs) compared with sorafenib, while lenvatinib demonstrated non-inferior OS. Following progression on sorafenib, statistically significant OS improvements over placebo were seen for cabozantinib and regorafenib in unselected patients and for ramucirumab in those with baseline α-fetoprotein≥400 ng/mL. Based on improved OS and PROs, atezolizumab plus bevacizumab appears to be a preferred first-line treatment option for intermediate or advanced non-LRT eligible HCC. Phase III data informing sequencing of later lines of treatment is lacking. Therefore, sequencing principles are proposed that can be used to guide treatment selection. Conclusions: Ongoing trials will continue to inform optimal therapy. Multiple targeted therapies have improved OS in intermediate or advanced non-LRT eligible HCC, although optimal sequencing is an area of ongoing investigation.